Spherical composite powder and preparation method thereof
By pretreating diamond powder and co-precipitation reaction of multi-elements, combined with spray granulation technology, metal shell coated diamond powder is formed, which solves the problems of uneven distribution of diamond components, thermal damage, and graphitization in additive manufacturing, and improves the The surface quality and bond strength of diamond tools.
Patent Information
- Application Number
- CN202211596102.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-13
AI Technical Summary
In the prior art, when manufacturing diamond composite materials with additive manufacturing, the surface bonding force between metal elements and diamond powder is poor, resulting in uneven distribution of diamond components, thermal damage, graphitization and other problems, affecting the surface quality and performance of the tool.
By pretreating the diamond powder, its surface characteristics are improved, and through multi-element co-precipitation reaction and spray granulation technology, a metal shell is formed to coat diamond powder, which improves the bonding force between the metal element and the diamond powder, and controls the shell thickness. and uniformity.
It effectively improves the surface quality of diamond tools, reduces thermal damage and graphitization, enhances bonding strength, and improves processing accuracy and performance.
Smart Images

Figure CN115805305B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, and in particular to a spherical composite powder and a preparation method thereof. Background Art
[0002] Silicon carbide (SiC) has high hardness and great brittleness second only to diamond and cubic boron nitride (CBN), high processing precision requirements, strong chemical inertness, and anisotropy of single-crystal silicon carbide, which makes it extremely difficult to cut, grind, and polish silicon carbide (SiC) semiconductor materials, and ordinary materials are difficult to meet the processing requirements. At present, the precision processing of silicon carbide (SiC) semiconductors is mainly achieved by diamond tools, which play a vital role throughout the entire process from wafer preparation to single chip. Domestic diamond tools have reached the import level in crystal rod cutting, crystal rod rounding, slicing, grinding and chamfering processes, but the thinning grinding wheels used in the wafer thinning process are still mainly imported, which is also the link in the entire processing process that requires extremely high diamond tools. Making diamond thinning grinding wheels to thin silicon carbide substrates is currently the only way.
[0003] Thinning wheels play an important role in the chip preparation process. On the one hand, the thinning process can reduce the overall thickness of the chip, which is beneficial to heat dissipation and integration; on the other hand, it can reduce the thickness of the damaged layer and surface roughness of the wafer surface, release the internal stress accumulated inside the wafer caused by the various processes before thinning, and reduce the degree of damage to a single chip during the dicing process.
[0004] The main preparation methods of traditional diamond thinning grinding wheels include hot pressing sintering, electroplating and brazing. In the hot pressing sintering and electroplating methods, there is only mechanical embedding between the abrasive and the binder, which is easy to cause thermal damage. Diamond particles often fall off during use, causing varying degrees of damage to the cut surface and low edge rate. The brazing method has too high a temperature, which can easily lead to diamond carbonization and reduced mechanical strength, affecting its performance. In addition, the traditional method requires a combination of multiple complex preparation processes to manufacture diamond tools. The design is limited by manufacturing and it is difficult to form special-shaped parts. It also requires molds, high production costs and long production cycles. At the same time, due to the large difference in density between diamond and metal binder, it is difficult to mix evenly, which is easy to cause segregation, and it cannot be effectively solved by traditional methods, which seriously affects the processing accuracy of grinding wheels for third-generation semiconductors such as silicon carbide. Therefore, the introduction of additive manufacturing technology can provide a new process method for the manufacture of diamond tools.
[0005] Additive manufacturing of diamond composite materials currently generally uses atomized spherical metal powder and diamond abrasive mechanical mixture as raw materials. During the additive manufacturing (SLM) forming process, the surface bonding force between the metal elements and the diamond powder is poor, the diamond components are unevenly distributed, and they are easily damaged by heat and graphitized. The manufactured diamond tools have poor surface quality, high residual stress, and poor bonding strength, which are far from the expected performance. Among them, the powder material is an important reason hindering its development.
[0006] Therefore, developing a spherical composite powder that improves the surface bonding between metal elements and diamond powder and avoids the problems of uneven distribution of diamond components, thermal damage, and graphitization during additive manufacturing is an urgent problem to be solved by people in this field. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a spherical composite powder and a preparation method thereof. The method pre-treats diamonds, improves the surface properties of diamond powders, and increases the surface bonding force between metal elements and diamond powders; controls the shell thickness, uniformity, and sphericity of the spherical composite powders by regulating the multi-element co-precipitation reaction and the spray granulation reaction conditions, thereby avoiding the problems of uneven distribution of diamond components, thermal damage, and graphitization in the spherical composite powders during additive manufacturing.
[0008] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0009] The first aspect of the present invention provides a spherical composite powder, wherein the spherical composite powder comprises diamond powder and a metal alloy.
[0010] For any one of the spherical composite powders, the structure thereof comprises:
[0011] at least one core-shell structured sub-powder, the sub-powder comprising the diamond powder core and a shell layer, the shell layer comprising the metal alloy;
[0012] A bonding body, the bonding body comprising the metal alloy; wherein,
[0013] The bonding body bonds the at least one core-shell structure sub-powder body to form a composite powder;
[0014] The shell layer is prepared by calcining and reducing the metal salt solution and the precipitant after co-precipitation reaction; and
[0015] The metal salt includes at least one of a transition metal salt and a Group IV metal salt.
[0016] Preferably, the transition metal salt includes at least one of iron salts, cobalt salts, nickel salts, copper salts, titanium salts, chromium salts, aluminum salts, molybdenum salts, manganese salts, niobium salts, tantalum salts, hafnium salts, yttrium salts, vanadium salts, tungsten salts and zirconium salts.
[0017] Preferably, the Group IV metal salt includes at least one of germanium salt, tin salt and lead salt.
[0018] Preferably, the particle size of the diamond powder is 1000 mesh to 8000 mesh, for example, 1000 mesh, 2000 mesh, 3000 mesh, 4000 mesh, 5000 mesh, 6000 mesh, 7000 mesh, or 8000 mesh.
[0019] Preferably, the transition metal salt includes at least one of iron salt, cobalt salt, nickel salt, copper salt and titanium salt.
[0020] Preferably, the Group IV metal salt comprises a tin salt.
[0021] The second aspect of the present invention provides a method for preparing the spherical composite powder, comprising the following steps:
[0022] Pre-treating diamond powder;
[0023] The metal salt solution, the pretreated diamond powder and the precipitant are mixed to obtain a mixed solution, heated to cause a coprecipitation reaction, and separated to obtain a precipitate;
[0024] calcining and reducing the precipitate in a reducing atmosphere to obtain composite micropowder;
[0025] The composite micropowder, the ultrafine alloy powder, a dispersant, and a binder are mixed to obtain a mixture, wherein the ultrafine alloy powder and the composite micropowder contain the same metal element;
[0026] The mixture is spray granulated to obtain composite powder, and the composite powder is calcined and reduced in a reducing atmosphere to obtain metal spherical powder.
[0027] Preferably, the pre-treatment of diamond powder comprises:
[0028] The diamond powder is treated with a mixed solution of dilute hydrochloric acid and hydrogen peroxide.
[0029] Preferably, the mass concentration of the dilute hydrochloric acid is 5% to 40%, the mass concentration of the hydrogen peroxide is 5% to 30%, and the mass ratio of the dilute hydrochloric acid to hydrogen peroxide is 2:1 to 3:1, for example, 2:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, or 3:1.
[0030] Preferably, the treatment time is 5 to 24 hours, for example, 5 hours, 8 hours, 11 hours, 14 hours, 17 hours, 21 hours, or 25 hours.
[0031] Preferably, the precipitant is oxalic acid.
[0032] Preferably, the precipitant is used in the form of a solution, the mass concentration of the solution is 1-10wt% (for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%), the pH value of the solution is 2-4 (for example, 2, 3, 4), and the mass of the precipitant in the solution is 110-130% of the total mass of metal ions in the metal salt solution (for example, 110%, 120%, 130%).
[0033] Preferably, the coprecipitation reaction temperature is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C, or 100°C.
[0034] Preferably, the coprecipitation reaction time is 20 to 70 min, for example, 20 min, 30 min, 40 min, 50 min, 60 min, or 70 min.
[0035] Preferably, in the step of obtaining the composite micropowder, the calcination reduction temperature is 400-600°C (for example, 400°C, 450°C, 500°C, 550°C, 600°C), and the time is 1-5h (for example, 1h, 2h, 3h, 4h, 5h).
[0036] Preferably, the reducing atmosphere in the step of obtaining the composite differential is hydrogen.
[0037] Preferably, after obtaining the precipitate after separation, a drying step is also included, and the drying temperature is 60-90°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C), and the time is 3-5h (for example, 3h, 4h, 5h).
[0038] Preferably, in the step of obtaining the metal spherical powder, the calcination reduction temperature is 250-450°C (for example, 250°C, 300°C, 350°C, 400°C, 450°C), and the time is 1-4h (for example, 1h, 2h, 3h, 4h).
[0039] Preferably, the reducing atmosphere in the step of obtaining the spherical composite powder is hydrogen or a mixed atmosphere of hydrogen and nitrogen.
[0040] Preferably, after the calcination and reduction in a reducing atmosphere to obtain the composite micropowder, crushing and screening are further included, and the screening uses a 600-2000 mesh sieve, for example, 600 mesh, 650 mesh, 700 mesh, 750 mesh, 800 mesh, 850 mesh, 900 mesh, 950 mesh, 1000 mesh, 1500 mesh, and 2000 mesh.
[0041] Preferably, after the composite powder is calcined and reduced in a reducing atmosphere to obtain a spherical composite powder, it also includes crushing and screening, and the screening uses a 200-800 mesh screen, for example, 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh, 650 mesh, 700 mesh, 750 mesh, and 800 mesh.
[0042] Preferably, the particle size of the ultrafine alloy powder is 5 to 20 μm, for example, 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, or 20 μm.
[0043] Preferably, the dispersant includes at least one of water and anhydrous ethanol.
[0044] Preferably, the binder includes at least one of polyethylene glycol and polyvinyl alcohol.
[0045] Preferably, in the mixture, the content of the binder is 3-5wt.% (for example, 3wt.%, 4wt.%, 5wt.%), and the content of the dispersant is 30-60wt.% (for example, 30wt.%, 35wt.%, 40wt.%, 45wt.%, 50wt.%, 55wt.%, 60wt.%).
[0046] Preferably, the inlet temperature of the spray granulation is 130-240°C (for example, 130°C, 150°C, 170°C, 200°C, 210°C, 220°C, 230°C, 240°C), the outlet temperature is 60-140°C (for example, 140°C, 140°C, 140°C, 140°C, 140°C, 140°C, 140°C), and the feed rate is 70-140mL / min (for example, 70mL / min, 80mL / min, 90mL / min, 100mL / min, 110mL / min, 120mL / min, 130mL / min, 140mL / min).
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1. The present invention provides a spherical composite powder and a preparation method thereof. The method improves the surface properties of diamond powder and improves the surface bonding force between metal elements and diamond powder by pre-treating diamond; a composite micropowder is obtained by co-precipitating multiple metal elements in a composite salt solution in a nanoparticle state on the surface of diamond, achieving uniform coating of metal elements and controllable composition ratio; thereafter, the composite micropowder is agglomerated and granulated with ultrafine alloy powder by spray granulation to obtain a spherical composite powder, and spray granulation increases the thickness of the metal shell layer, so that the diamond powder is protected from or weakened from laser ablation during the additive manufacturing process, avoids thermal damage, and prevents graphitization of the surface of the diamond powder; in addition, a metal shell layer is formed by precipitating multiple metal elements on the surface of the diamond powder, thereby improving the bonding strength between the composite micropowder and the ultrafine alloy powder during the spray granulation process, making the metal coated on the surface of the composite micropowder uniformly alloyed, and increasing the degree of spheroidization of the spherical composite powder obtained by spray granulation, maintaining good fluidity. Therefore, the present invention controls the shell thickness, uniformity and sphericity of the metal spherical powder by regulating the multi-element co-precipitation reaction and the spray granulation reaction conditions, thereby avoiding the problems of uneven distribution of diamond components, thermal damage and graphitization in the metal spherical powder during the additive manufacturing process.
[0049] 2. The spherical composite powder provided by the present invention obtains composite micropowder by precipitating multiple metal elements on the surface of diamond powder to form a metal material shell layer, thereby solving the problems of uneven alloying of composite micropowder and multiple metal elements, thermal damage to diamond, and high internal stress of the prepared diamond abrasive tool. It also achieves controllable pore size and distribution of the diamond abrasive tool, which can meet the needs of chip removal and high sharpness, long life, and high-precision processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a schematic diagram of the process for preparing spherical composite powder in Example 1.
[0051] Figure 2 This is the EDS image of Cu-Sn-diamond spherical composite powder prepared by co-precipitation method in Example 1.
[0052] Figure 3 This is a schematic diagram of the spherical composite powder structure prepared in Example 1. DETAILED DESCRIPTION
[0053] In order to make the contents of the present invention easier to understand, the technical solutions of the present invention are further described below in conjunction with specific embodiments, but the present invention is not limited thereto. All technologies realized based on the above contents of the present invention are included in the present invention.
[0054] Unless otherwise specified, the raw materials and reagents used in the examples are all commercially available. Reagents, instruments or operating procedures not described herein are all contents that can be routinely determined by ordinary technicians in the field.
[0055] Embodiment 1:
[0056] S1: Diamond pretreatment: Use 50 mL of a mixed solution of dilute hydrochloric acid: hydrogen peroxide = 2:1 to treat the surface of 2 g 2000 mesh diamond powder for 8 h;
[0057] S2: Preparation of a metal salt mixture: According to the mass ratio of Cu:Sn=90:10, weigh 2.42g CuCl2·2H2O and 0.16g SnCl2·2H2O metal salt, add 0.01g sodium dodecyl sulfate (SDS), dissolve in deionized water and stir to prepare 50mL of a mixed metal salt solution, and heat to 90°C;
[0058] S3: Preparation of oxalic acid solution: Calculate the mass of oxalic acid based on 20% excess of metal salt ions, weigh 0.83 g of oxalic acid and dissolve it in 50 mL of deionized water, prepare oxalic acid solution and heat it to 60°C, add NH3·H2O dropwise to adjust the pH to 3;
[0059] S4: Diamond washing: Filter and wash the treated diamond powder with deionized water for 5 times until it is neutral;
[0060] S5: Co-precipitation reaction: Add the washed diamond powder to the heated metal salt solution and stir vigorously. The stirring rate is based on the dispersion of diamond powder in the solution. The oxalic acid solution is added at a rate of 30 mL / min to the diamond powder mixed salt solution for co-precipitation reaction for 30 min.
[0061] S6: Filtration, washing and drying: The reaction-completed solution was filtered and washed 5 times until it became neutral, and then vacuum dried at 70° C. for 2 h;
[0062] S7: Calcination reduction: Calcination reduction at 450°C for 2h under H2 atmosphere;
[0063] S8: Grinding and crushing: crushing and screening the reduced powder, selecting a sieve of 800 mesh, to obtain CuSn-coated composite micropowder;
[0064] S9: Slurry preparation: weigh 2 g of CuSn-coated composite micropowder and 18 g of ultrafine CuSn10 alloy powder with a D50 of about 5 μm, add them into 50 mL of deionized water, then add 1.3 g of polyethylene glycol (PEG2000), and stir the mixed slurry with a stirrer at a stirring rate of 4000 rpm to obtain a mixture slurry with uniform viscosity;
[0065] S10: Spray granulation: The mixed slurry is transferred to a spray dryer for spray drying and granulation to obtain spherical composite powders. The inlet temperature of the spray tower is 200°C, the outlet temperature is 100°C, the peristaltic pump feed rate is 90 mL / min, and the agitator is kept stirring the slurry during the spraying process;
[0066] S11: Calcination reduction: The diamond-containing composite powder obtained by spray granulation is placed in a reduction furnace and calcined and reduced at 300° C. for 2 h in a pure H2 atmosphere to remove crystal water, and finally crushed and sieved to form a diamond-containing spherical composite powder.
[0067] Embodiment 2:
[0068] S1: Diamond pretreatment: Use 70 mL of a mixed solution of dilute hydrochloric acid: hydrogen peroxide = 3:1 to treat the surface of 5 g 2000 mesh diamond powder for 10 h;
[0069] S2: Preparation of a metal salt mixture: According to the mass ratio of Cu:Sn=90:10, weigh 6.05gCuCl2·2H2O and 0.4gSnCl2·2H2O metal salt, add 0.02g SDS, dissolve in deionized water and stir to prepare 50mL of a mixed metal salt solution, and heat to 85°C;
[0070] S3: Preparation of oxalic acid solution: Calculate the mass of oxalic acid based on 20% excess of metal salt ions, weigh 2.08 g of oxalic acid and dissolve it in 50 mL of deionized water, prepare oxalic acid solution and heat it to 60°C, add NH3·H2O dropwise to adjust the pH to 4;
[0071] S4-S8: the same as the steps in Example 1;
[0072] S9: Slurry preparation: weigh 5 g of CuSn-coated composite micropowder and 45 g of 8 μm (D50) ultrafine CuSn10 alloy powder, add them into 100 mL of deionized water, then add 2 g of polyvinyl alcohol, and stir the mixed slurry with a stirrer at a stirring rate of 4500 rpm to obtain a mixture slurry with uniform viscosity;
[0073] S10: Spray granulation: The mixed slurry is transferred to a spray dryer for spray drying and granulation to obtain spherical composite powders. The inlet temperature of the spray tower is 210°C, the outlet temperature is 110°C, the peristaltic pump feed rate is 100mL / min, and the agitator is kept stirring the slurry continuously during the spraying process;
[0074] S11: Calcination reduction: The diamond-containing composite powder obtained by spray granulation is placed in a reduction furnace and calcined and reduced at 350° C. for 2 h in a N2 / H2 mixed atmosphere to remove crystal water, and finally crushed and sieved to form a diamond-containing spherical composite powder.
[0075] Embodiment 3:
[0076] S1: Diamond pretreatment: Use 120 mL of a mixed solution of dilute hydrochloric acid: hydrogen peroxide = 2:1 to treat the surface of 10 g of diamond powder for 20 h;
[0077] S2: Preparation of a metal salt mixture: According to the mass ratio of Cu:Sn=90:10, weigh 12.1g CuCl2·2H2O and 0.8g SnCl2·2H2O metal salt, add 0.04g SDS, dissolve in deionized water and stir to prepare 100mL of a mixed metal salt solution, and heat to 80°C;
[0078] S3: Preparation of oxalic acid solution: Calculate the mass of oxalic acid based on 20% excess of metal salt ions, weigh 4.16 g of oxalic acid and dissolve it in 100 mL of deionized water, prepare oxalic acid solution and heat it to 55° C. Add NaOH dropwise to adjust the pH to 3;
[0079] S4-S8: Same as the steps in Example 1;
[0080] S9: Slurry preparation: weigh 10 g of CuSn-coated composite micropowder and 90 g of 10 μm (D50) ultrafine CuSn10 alloy powder and add them into 170 mL of anhydrous ethanol, then add 5.0 g of PEG2000, and stir the mixed slurry with a stirrer at a stirring rate of 5000 rpm to obtain a mixture slurry with uniform viscosity;
[0081] S10: Spray granulation: The mixed slurry is transferred to a spray dryer for spray drying and granulation to obtain spherical composite powders. The inlet temperature of the spray tower is 220°C, the outlet temperature is 120°C, the peristaltic pump feed rate is 120 mL / min, and the agitator is kept stirring the slurry during the spraying process;
[0082] S11: Calcination reduction: The diamond-containing spherical composite powder obtained by spray granulation is placed in a reduction furnace for calcination reduction at 400° C. for 2 h in a N2 / H2 mixed atmosphere to remove crystal water, and finally crushed and sieved to form a diamond-containing spherical composite powder.
[0083] Embodiment 4:
[0084] S1: Diamond pretreatment: Use 120 mL of a mixed solution of dilute hydrochloric acid: hydrogen peroxide = 2:1 to treat the surface of 10 g of diamond powder for 20 h;
[0085] S2: Preparation of a metal salt mixture: According to the mass ratio of Cu:Sn=90:10, weigh 14.52g CuCl2·2H2O and 0.96g SnCl2·2H2O metal salt, add 0.08g SDBS, dissolve in deionized water and stir to prepare 100mL of a mixed metal salt solution, and heat to 80°C;
[0086] S3: Preparation of oxalic acid solution: Calculate the mass of oxalic acid based on 20% excess of metal salt ions, weigh 4.99 g of oxalic acid and dissolve it in 100 mL of deionized water, prepare oxalic acid solution and heat it to 60°C, and add NaOH dropwise to adjust the pH to 3;
[0087] S4-S8: Same as the steps in Example 1;
[0088] S9: Slurry preparation: weigh 10 g of CuSn-coated composite micropowder and 90 g of 10 μm (D50) ultrafine CuSn10 alloy powder and add them into 170 mL of anhydrous ethanol, then add 5.0 g of PEG2000, and stir the mixed slurry with a stirrer at a stirring rate of 5000 rpm to obtain a mixture slurry with uniform viscosity;
[0089] S10: Spray granulation: The mixed slurry is transferred to a spray dryer for spray drying and granulation to obtain spherical composite powders. The inlet temperature of the spray tower is 200°C, the outlet temperature is 120°C, the peristaltic pump feed rate is 120 mL / min, and the agitator is kept stirring the slurry during the spraying process;
[0090] S11: Calcination reduction: The diamond-containing composite powder obtained by spray granulation is placed in a reduction furnace and calcined and reduced at 400° C. for 2 h in a N2 / H2 mixed atmosphere to remove crystal water, and finally crushed and sieved to form a diamond-containing spherical composite powder.
[0091] Embodiment 5:
[0092] S1: Diamond pretreatment: Use 150 mL of a mixed solution of dilute hydrochloric acid: hydrogen peroxide = 2:1 to treat the surface of 12 g of diamond powder for 10 h;
[0093] S2: Preparation of a metal salt mixture: According to the mass ratio of Cu:Sn=80:20, weigh 10.76g CuCl2·2H2O and 1.6g SnCl2·2H2O metal salt, add 0.15g SDBS, dissolve in deionized water and stir to prepare 100mL of a mixed metal salt solution, and heat to 80°C;
[0094] S3: Preparation of oxalic acid solution: Calculate the mass of oxalic acid based on 20% excess of metal salt ions, weigh 7.65 g of oxalic acid and dissolve it in 100 mL of deionized water, prepare oxalic acid solution and heat it to 60° C. Add NaOH dropwise to adjust the pH to 3;
[0095] S4-S8: Same as the steps in Example 1;
[0096] S9: Slurry preparation: weigh 20g of CuSn-coated composite micropowder and 80g of 10μm (D50) ultrafine CuSn10 alloy powder and add them into 150mL of anhydrous ethanol, then add 7.5g of PEG2000, and stir the mixed slurry with a stirrer at a stirring rate of 6000rpm to obtain a mixture slurry with uniform viscosity;
[0097] S10: Spray granulation: The mixed slurry is transferred to a spray dryer for spray drying and granulation to obtain spherical composite powders. The inlet temperature of the spray tower is 200°C, the outlet temperature is 120°C, the peristaltic pump feed rate is 120 mL / min, and the agitator is kept stirring the slurry during the spraying process;
[0098] S11: Calcination reduction: The diamond-containing composite powder obtained by spray granulation is placed in a reduction furnace and calcined and reduced at 400° C. for 2 h in a pure H 2 atmosphere to remove crystal water, and finally crushed and sieved to form a diamond-containing spherical composite powder.
[0099] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing spherical composite powder, characterized in that: The spherical composite powder comprises diamond powder and metal alloy. For any one of the spherical composite powders, the structure thereof comprises: at least one core-shell structured sub-powder, the sub-powder comprising the diamond powder core and a shell layer, the shell layer comprising the metal alloy; A bonding body, the bonding body comprising the metal alloy; wherein, The bonding body bonds the at least one core-shell structure sub-powder body to form a composite powder; The shell layer is prepared by calcining and reducing the metal salt solution and the precipitant after co-precipitation reaction; and The metal salt includes at least one of a transition metal salt and a fourth group metal salt; The preparation method of the spherical composite powder comprises the following steps: Pre-treating the diamond powder with a mixed solution of dilute hydrochloric acid and hydrogen peroxide; the mass concentration of the dilute hydrochloric acid is 5% to 40%, the mass concentration of the hydrogen peroxide is 5% to 30%, and the mass ratio of the dilute hydrochloric acid to the hydrogen peroxide is 2:1 to 3:1; the pre-treatment time is 5 to 24 hours; The metal salt solution, the pretreated diamond powder and the precipitant are mixed to obtain a mixed solution, and the mixed solution is heated to cause a coprecipitation reaction, and a precipitate is obtained after separation; the coprecipitation reaction temperature is 60-100° C., and the coprecipitation reaction time is 20-70 min; calcining and reducing the precipitate in a reducing atmosphere to obtain composite micropowder; The composite micropowder, the ultrafine alloy powder, a dispersant and a binder are mixed to obtain a mixture, wherein the ultrafine alloy powder and the composite micropowder contain the same metal element; The mixture is spray granulated to obtain a composite powder, and the composite powder is calcined and reduced in a reducing atmosphere to obtain a spherical composite powder; the inlet temperature of the spray granulation is 130-240°C, the outlet temperature is 60-140°C, and the feed rate is 70-140 mL / min.
2. The preparation method according to claim 1, characterized in that: The transition metal salt includes at least one of iron salt, cobalt salt, nickel salt, copper salt, titanium salt, chromium salt, aluminum salt, molybdenum salt, manganese salt, niobium salt, tantalum salt, hafnium salt, yttrium salt, vanadium salt, tungsten salt and zirconium salt; The fourth group metal salt includes at least one of germanium salt, tin salt and lead salt; The particle size of the diamond powder is 1000 mesh to 8000 mesh.
3. The preparation method according to claim 1, characterized in that: The precipitant is oxalic acid; The precipitant is used in the form of a solution, the mass concentration of the solution is 1-10wt%, the pH value of the solution is 2-4, and the mass of the precipitant in the solution is 110-130% of the total mass of the metal ions in the metal salt solution.
4. The preparation method according to claim 1, characterized in that: In the step of obtaining the composite micropowder, the calcination reduction temperature is 400-600° C. and the time is 1-5 hours.
5. The preparation method according to claim 1, characterized in that: After the precipitate is obtained after separation, a drying step is further included, wherein the drying temperature is 60-90° C. and the drying time is 3-5 hours; In the step of obtaining the spherical composite powder, the calcination reduction temperature is 250-450° C. and the time is 1-4 hours.
6. The preparation method according to claim 1, characterized in that: After the composite micropowder is obtained by calcining and reducing in a reducing atmosphere, crushing and screening are further performed, wherein the screening is performed using a 600-2000 mesh screen; After the composite powder is calcined and reduced in a reducing atmosphere to obtain a spherical composite powder, the method further includes crushing and screening, wherein the screening is performed using a 200-800 mesh screen; The particle size of the ultrafine alloy powder is 5-20 μm.
7. The preparation method according to claim 1, characterized in that: The dispersant includes at least one of water and anhydrous ethanol; The binder includes at least one of polyethylene glycol and polyvinyl alcohol; In the mixture, the content of the binder is 3-5 wt.%, and the content of the dispersant is 30-60 wt.%.
Citation Information
Patent Citations
Fine-granularity polycrystalline diamond and preparation method thereof
CN109706340A
Nickel, molybdenum, iron, chromium and diamond alloy composite powder and preparation method and application thereof
CN110014146A